Development and Evaluation of an Explicit Treatment of Aerosol Processes at Cloud Scale Within a Multi‐Scale Modeling Framework (MMF). (25th July 2018) - Lin, Guangxing; Ghan, Steven J.; Wang, Minghuai; Ma, Po‐Lun; Easter, Richard C.; Ovchinnikov, Mikhail; Fan, Jiwen; Zhang, Kai; Wang, Hailong; Chand, Duli; Qian, Yun
Abstract: Modeling the aerosol lifecycle in traditional global climate models (GCM) is challenging for a variety of reasons, not the least of which is the coarse grid. The multiscale modeling framework (MMF), in which a cloud resolving model replaces conventional parameterizations of cloud processes within each GCM grid column, provides a promising framework to address this challenge. Here we develop a new version of MMF that for the first time treats aerosol processes at cloud scale to improve the aerosol‐cloud interaction representation in the model. We demonstrate that the model with the explicit aerosol treatments shows significant improvements of many aspects of the simulated aerosols compared to the previous version of MMF with aerosols parameterized at the GCM grid scale. The explicit aerosol treatments produce a significant increase of the column burdens of black carbon (BC), primary organic aerosol, and sulfate by up to 40% in many remote regions, a decrease of the sea‐salt aerosol burdens by 40% in remote regions. These differences are caused by the differences in aerosol convective transport and wet removal between these two models. The new model also shows reduced bias of BC surface concentration in North America and BC vertical profiles in the high latitudes. However, the biased‐high BC concentrations in the upper troposphere over the remote Pacific regions remain, requiring further improvements on other process representations (e.g., secondary activation neglected in the model). Plain Language Summary: Most global climate models (GCMs) cannot resolve the important aerosol processes that are related to clouds and occur at cloud scale. This makes it difficult to predict the aerosol change and aerosol effects on climate. In contrast, the multi‐scale modeling framework (MMF), which embeds a cloud resolving model (CRM) into each GCM grid column to resolve the cloud formation, provides a promising tool to handle this challenge. In this study, we develop a first global model explicitly representing aerosol processes at cloud scale (in each CRM grid cell) within a MMF. We found that (1) the MMF with aerosol processes explicitly represented in CRM grid cells can improve aerosol simulations in many aspects. (2) the MMF with aerosols parameterized in GCM grid cells can cause great biases in modelled aerosol distributions. Key Points: A new MMF with aerosols explicitly represented at cloud scale is developed Parameterizing aerosols in coarse global climate model grids leads to biases in aerosol distributions The explicit aerosol treatment at cloud scale improves many aspects of the simulated aerosols